Áreas degradadas pela explotação de cassiterita: avaliação das condições dos agregados e atividades biológicas - Mello, Giovanna Frederici de [UNESP] (2015)
One of the biggest natural wealth of Brazil is its mineral potential. The Amazon region is known for the abundance of mineral resources, and can highlight the topaz, oil, and especially tin. As a result of mining, the ecosystem has undergone a constant process of degradation. An important tool in the exploration of mineral resources is the rehabilitation and / or restoration of degraded areas, for this it is necessary to establish degradation indicators, as well as soil quality associated with its biota, taking into account that this is a dynamic environment, heterogeneous and complex physical, chemical and biological diverse. Thus, the objective of this work was to study the association between variables of biological soil activity and morphometric variables of households, aiming at a Pedotransfer function to identify expeditiously the best indicators of recovery for the experimental areas located in mining floor substrate the National Forest of Jamari-RO.Os results showed great variability in all the morphometric variables and a lower dispersion of data for biological variables. The analysis method of the amplitude differences between the parameters analyzed in the areas allowed the comparison of the areas facilitating recovery graphical interpretation of differences. It was possible through the canonical correlation determine linear combinations of the set of variables of soil biodiversity and to all the variables of the morphometric parameters of soil aggregates whereas the linear combination model has not submitted a satisfactory adjustment, the definition of an index expeditious been compromised, as there is need to study the problems of multicollinearity and intercorrelation between the predictive equations of biological activity through morphometric variables.